ANALISIS STRATEGI PEMERINTAH KOTA BOGOR DALAM MENGELOLA TEMPAT PEMAKAMAN UMUM PADA DINAS KEBERSIHAN DAN PERTAMANAN KOTA BOGOR - M. Subki Tahyudin; Abubakar Iskandar; M. Yamin Saleh (LPPM Universitas Djuanda Bogor, 2016)
The focus of the research is the management of TPU in the city of Bogor, the purpose of this study was to determine the strategy of the City Government in the management of TPU, to investigate the implementation of the government's strategy of Bogor manage TPU and for mengetaui impact strategy Bogor city administration to the user community TPU. The method used in this study is a qualitative method by taking the informant of the two types of informants for Administrative manager of TPU and user communities TPU using techniques snow ball, TPU city of Bogor there are eight TPU, the study focused on four TPU them TPU Gunung Gadung, TPU Cipaku, TPU and TPU Dreded Blender. researchers showed that the provision of land in Bogor City TPU has not been ideal with the needs of the community cemetery. At this time the city of Bogor require five (5) hectares of TPU, the strategy of the City Government in managing the TPU results structured interview stated that the strategy pegelolaan TPU is expected to provide services to the needs of society in a cemetery that is desired and expected by the public, in the implementation of the policy as a strategy management of TPU, the management of TPU is not ideal with the regulations the City Government as the provisions of the management planned, many factors and constraints in managing TPU like availability of land in the city of Bogor is very difficult to get, quality and human resource capacity to be a factor to failure in managing the TPU, lack of socialization management policy to the community of the importance of the TPU management policy, as well as the lack of attention from the Bogor city administration for the management of TPU. the impact of management strategies TPU on society shows that the answer No 54.1% and 45.9% YES answer is public response to the TPU management policy means greater datipada answers No answer Yes to show people are not satisfied with the services provided by the City Government Bogor UPTD Funeral manage TPU.Keywords: Policies, TPU, Human Resources.